(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
This article provides insights into reforms, challenges, and solutions in the preschool education system. Preschool education is the primary part of lifelong learning. It stimulates the child’s desire to learn, prepares him for systematic learning, ensuring that the child is formed into a healthy and developed person. Therefore, the further strengthening of this system, the creation of favorable conditions in preschool education, the wide involvement of preschool children in them play an important role in the formation of our children as harmonious and mature individuals.